Human sapovirus propagation in human cell lines supplemented with bile acids - Takagi, Hirotaka (Proc Natl Acad Sci U S A, 2020)
Human sapoviruses (HuSaVs) cause acute gastroenteritis similar to human noroviruses. Although HuSaVs were discovered four decades ago, no HuSaV has been grown in vitro, which has significantly impeded the understanding of viral biology and the development of antiviral strategies. In this study, we identified two susceptible human cell lines, that originated from testis and duodenum, that support HuSaV replication and found that replication requires bile acids. HuSaVs replicated more efficiently in the duodenum cell line, and viral RNA levels increased up to ∼6 log(10)-fold. We also detected double-stranded RNA, viral nonstructural and structural proteins in the cell cultures, and intact HuSaV particles. We confirmed the infectivity of progeny viruses released into the cell culture supernatants by passaging. These results indicate the successful growth of HuSaVs in vitro. Additionally, we determined the minimum infectious dose and tested the sensitivities of HuSaV GI.1 and GII.3 to heat and ultraviolet treatments. This system is inexpensive, scalable, and reproducible in different laboratories, and can be used to investigate mechanisms of HuSaV replication and to evaluate antivirals and/or disinfection methods for HuSaVs.